PENGENALAN JURUSAN ILMU KELAUTAN PADA SISWA SMAN N 1 (SMANSA) PONTIANAK MELALUI KEGIATAN PROGRAM PARENT TEACHING DAY (PTD) - Susanti, Ema; Widodo, Muhammad Aris (Bina Bahari, 2023)
A good education system will produce superior human resources who can be relied upon in the progress of the nation and the welfare of the Indonesian people in the future. The role of teachers and parents, facilities and infrastructure in the implementation of the learning process greatly determines the quality of learning outcomes. Parent Teaching Day (PTD) is one of the programs from SMAN No. 1 which provides opportunities for parents to teach at school, related to various kinds of knowledge or competencies possessed by their respective parents. One of the PTD materials carried out by SMANSA class XI D is an introduction to the Department of Marine Science, Tanjungpura University. The purpose of this activity is to introduce the marine science department which includes knowledge about the marine environment by one of the student's parents as well as an attempt to increase student motivation. The activity was carried out using the lecture and demonstration method about 3 fields of study in the marine science department, attended by 36 students of class XI D and their homeroom teacher, carried out smoothly and the participants responded very enthusiastically. The evaluation of the introduction to the marine science department was carried out through a verbal questionnaire by the presenters, showing an increase in the understanding of class XI D SMANSA students as participants in the activity. Keywords: system, PTD, SMANSA, marine science.